Mingus speaks - Mingus, Charles, 1922-1979 (University of California Press, 2013)
Charles Mingus is among jazz's greatest composers and perhaps its most talented bass player. He was blunt and outspoken about the place of jazz in music history and American culture, about which performers were the real thing (or not), and much more. These in-depth interviews, conducted several years before Mingus died, capture the composer's spirit and voice, revealing how he saw himself as composer and performer, how he viewed his peers and predecessors, how he created his extraordinary music, and how he looked at race. Augmented with interviews and commentary by ten close associates-includi.